Meningkatkan Kemampuan Pemecahan Masalah Matematis Kelas XI SMA Istiqomah Bandung Menggunakan Pembelajaran Berbasis Masalah - Wildan, Asep; Novtiar, Chandra (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2018)
In purpose of learning mathematics exist one aspect must be improved is mathematical problem solving ability. But in fact, a level of students’ ability in pertained to weak. A trigonometry is one of the material which is quite difficult understood students XI grade in SMA ISTIQOMAH Bandung. It is need to be held a solution in learning that is using Problem Based Learning (PBL). This research using the method classroom action research with two cycles, which each cycles has two meetings. At the end of each cycle, students are given a written test in the form of a description. The result of research, show an increase on the mathematical problem solving ability by applying PBL. Seen from the results of the average score on each cycle, pre-cycle results with a score 37, in cycle one the score becomes 69 (42,30%), and in cycle two the score becomes 77 (69,23%).